Development of a Multi-functional Soft Robot (SNUMAX) and Performance in RoboSoft Grand Challenge - Lee, Jun-Young; Kang, Brian Byunghyun; Lee, Dae-Young; Baek, Sang-Min; Kim, Woong-Bae; Choi, Woo-Young; Song, Jeong-Ryul; Joo, Hyeong-Joon; Park, Daegeun; Cho, Kyu-Jin (Frontiers in Robotics and AI, 2016)
This paper introduces SNUMAX, the grand winner of the RoboSoft Grand Challenge. SNUMAX was built to complete all the tasks of the challenge. Completing these tasks required robotic compliant components that could adapt to variable situations and environments and generate enough stiffness to maintain performance. SNUMAX has three key components: transformable origami wheels, a polymer-based variable stiffness manipulator, and an adaptive caging gripper. This paper describes the design of these components and how they worked together to allow the robot to perform the contest’s navigation and manipulation tasks.